Deaf and hard-of-hearing adolescents' experiences of inclusion and exclusion in mainstream and special schools in Sweden. Issue 4 (8th August 2018) - Olsson, Sylvia; Dag, Munir; Kullberg, Christian
Abstract: This study examines the question of which school environment – special or mainstream school – is more favourable for deaf and hard-of-hearing students in Sweden, when it comes to their well-being, and their social and academic inclusion. The aim is threefold: first to compare the well-being of adolescents who are deaf or hard-of-hearing, who are deaf or hard-of-hearing and have additional disabilities, and who have no disabilities; second to compare the adolescents from the two deaf and hard-of-hearing groups and their experiences of inclusion and exclusion in school; and third to ascertain if any gender differences exist between the two groups of deaf and hard-of-hearing students concerning their experiences of inclusion and exclusion. A total of 7865 adolescents (13–18 years of age) answered a total survey about the life and health of young people in a county in Sweden. The results show that both boys and girls in the hard-of-hearing groups rated their well-being lower and were less satisfied with their lives than pupils without disabilities. They also show that the hard-of-hearing boys and girls attending special school were more satisfied with their lives and to a greater extent felt included both socially and academically than students in mainstream school.